Clinical application of integrated traditional Chinese and western medicine nursing based on biopsychosocial model in patients with periodontitis (基于“生物-心理-社会医学模式”的中西医结合护理在牙周炎患者中的应用效果观察) - CUI Yue (崔悦); CAI Shuang (蔡爽); LIU Xuewei (刘学伟); WANG Meng (王蒙); LIANG Yu (梁宇); MU Hong (穆宏) (中西医结合护理)
Objective To explore the effect of integrated traditional Chinese and western medicine nursing based on biopsychosocial model in patients with periodontitis during the basic periodontal and supportive treatment periods. Methods Patients who visited the outpatient clinic from September 2023 to September 2024 were randomly divided into the control group (n=51) and the treatment group (n=52). The control group received conventional periodontal care, while the treatment group received periodontal systematic care based on biopsychosocial model combined with Traditional Chinese herb mouthwash. The periodontal systematic care includes: ①making a plan based on biopsychosocial model through literature review and interviews with the patients; ②implementation of personalized oral health education to patients through demonstration, patient imitation, and correction; ③Using perspective-taking and positive guidance to relieve the anxiety from patients; ④Providing social support to patients by encouraging family participation and activating communication with fellow patients. The changes in periodontal clinical indicators, self-efficacy on oral healthcare, anxiety status, oral-related quality of life were compared between two groups. Results After 3 months, the periodontal clinical indicators (Plaque index, Gingival index, Probing depth, Clinical attachment loss) of the treatment group were lower than those of the control group, with statistically significant differences (P＜0. 05). Scores of the Self-efficacy scale for self-care, modified dental anxiety scale, oral health impact profile-14 were better than those of the control group, with statistically significant differences (P＜0. 05). Conclusion The integrated traditional Chinese and western medicine nursing based on biopsychosocial model has not only helped patients control periodontitis, but also reduced their anxiety, improved their quality of life, and enhances the quality of nursing services. (目的 探讨基于“生物-心理-社会医学模式”的中西医结合护理在牙周炎患者牙周基础治疗和牙周支持治疗期间的应用效果。方法 选取2023年9月—2024年9月科室牙周专病门诊就诊的患者, 随机分为对照组(n=51)和治疗组(n=52)。对照组给予常规口腔护理, 治疗组给予基于“生物-心理-社会医学模式”的牙周系统护理并联合使用中药漱口水。基于“生物-心理-社会医学模式”的牙周护理包括: ①通过学习文献和访谈, 制定多维度护理计划; ②通过示范、患者模仿、再纠正等方法, 对患者实施个性化的口腔健康宣教; ③通过正向引导, 缓解患者的焦虑情绪; ④通过鼓励家属参与, 以及和病友之间的积极交流, 给患者提供社会化的支持。对比两组牙周临床指标、口腔保健自我效能、焦虑程度和口腔健康相关生活质量。结果 3个月后, 治疗组的牙周临床指标(菌斑指数、牙龈指数、探诊深度、附着丧失)改善优于对照组, 差异有统计学意义(P＜0. 05)。治疗组口腔保健自我效能量表(SESS)、修正版牙科焦虑量表(MDAS)和口腔健康影响程度量表(OHIP‐14)评分均优于对照组, 差异有统计学意义(P＜0. 05)。结论 基于“生物-心理-社会医学模式”的牙周护理的中西医结合护理干预不仅有助于控制牙周炎, 还可以减轻患者焦虑, 提高患者生活质量, 提高专科护理服务的质量。)